Ambient Air Pollution and Histopathologic Effects of Quarry Industry on Liver and Kidney of Albino Rats - Madu, Francis Ugochukwu; Akubugwo, Emmanuel Iroha; Uhegbu, Friday Obinwa; Osuocha, Kelechi Uzoma (International Journal of Scientific Research in Biological Sciences, 2020)
The present research studied the histopathologic effects of air pollution in a Quarry industry on the liver and kidney of albino rats. Thirty male albino rats were housed at various locations of the industry in five groups of five rats each for 90 days. Control animals were housed at a distance of 5.7km from the industry. Air sampling was done using gas monitor and analyzer at the same locations as in animal sampling. This was done three times at each point per day, and once a week for 90 days. From the results, levels of NO2 in the quarry ambient air were above the WHO standard values of 0.04-0.06mg/m3. Concentrations of SO2 in the quarry increased significantly compared (p<0.05) to the control and were also above the WHO standard value of 0.01mg/m3. The levels of particulate matter 1 (PM1) in the quarry increased significantly compared (p<0.05) to the control and also higher than the WHO standard value of 0.25µg/m3. The Concentrations of particulate matter 2.5 (PM2.5) in the quarry industry were below the WHO standard value of 10.00µg/m3 except at the crusher with a concentration of 11.40±1.00µg/m3 in the afternoon. Levels of the heavy metals in the dust were significantly higher in the quarry compared (p<0.05) to the control. The values of chromium, arsenic and lead were above the Nigerian Environmental Standard and Regulation Enforcement Agency (NESREA) standard values. Histopathological findings indicate that the albino rats suffered from cholate stasis and nephrosis but rats housed at the drilling pit and crusher sections of the quarry industry were greatly affected. These findings suggest that quarry workers who work without appropriate and effective safety equipments will likely suffer from liver and kidney injury and diseases.